Pengaruh Electronic Word of Mouth (E-WOM), Store Atmosphere, dan Price Perception terhadap Keputusan Pembelian pada Kafe MAB Surabaya - Mujahidah, Sofi Saadatul; Ida Bagus Cempena (Nirta Learning Centre, 2025)
This study aims to analyze and verify the influence of Electronic Word of Mouth (E-WOM), Store Atmosphere, and Price Perception on Purchase Decisions at MAB Café in Surabaya. The research employs a quantitative method with a sample size of 100 respondents collected through questionnaires. The data analysis techniques used include Descriptive Analysis, Instrument Testing, Classical Assumption Testing, and Hypothesis Testing, conducted using SPSS 26. The study was carried out from October to November 2024. The findings indicate that all indicators are valid and reliable. Based on Multiple Linear Regression analysis, the Price Perception variable has a more dominant influence, while the Store Atmosphere variable has a lesser influence. The T-test results reveal that Electronic Word of Mouth (E-WOM) has a significant partial effect on Purchase Decisions, Store Atmosphere has an effect but is not significant, and Price Perception has a significant partial effect on Purchase Decisions at MAB Café in Surabaya. The F-test results confirm that Electronic Word of Mouth (E-WOM), Store Atmosphere, and Price Perception collectively have a significant influence on Purchase Decisions at MAB Café. Meanwhile, the Coefficient of Determination (R²) test results show that the independent variables account for 78.5% of the variation in the dependent variable, with the remaining 21.5% influenced by other variables outside the research model Keywords: Electronic Word of Mouth (E-WOM); Store Atmosphere; Price Perception; Purchase Decision.